1987
DOI: 10.1099/0022-1317-68-10-2607
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of Particles of Hepatitis B Surface Antigen from Insect Cells Using a Baculovirus Vector

Abstract: SUMMARYThe coding sequences of the hepatitis B virus surface antigen were inserted into a baculovirus transfer vector produced from Autographa californica nuclear polyhedrosis virus (AcNPV) so that the foreign gene was under the control of the AcNPV polyhedrin promoter. Spodoptera frugiperda cells infected with the derived recombinant baculovirus produced and secreted 22 nm particles containing the hepatitis B surface antigen. The particles had morphological and antigenic properties identical to those of 22 nm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…Efficient secretion of HBsAg particles into the cell supernatant was also reported for mammalian cells (Marion et al 1979;Liu et al 1982), but not for yeast (Valenzuela et al 1982;Hitzeman et al 1983;Janowicz et al 1991) or Lepidoptera cells upon recombinant baculovirus infection (Lanford et al 1989). Our findings in terms of HBsAg synthesis were comparable to those reported for Lepidoptera cells using the baculovirus expression system (Kang et al 1987;Lanford et al 1989) or mouse cells transfected using a bovine papilloma virus vector system (Hsiung et al 1984). Our approach allowed us to obtain HBsAg expression levels comparable to those previously published (Deml et al 1999).…”
Section: Discussionsupporting
confidence: 78%
“…Efficient secretion of HBsAg particles into the cell supernatant was also reported for mammalian cells (Marion et al 1979;Liu et al 1982), but not for yeast (Valenzuela et al 1982;Hitzeman et al 1983;Janowicz et al 1991) or Lepidoptera cells upon recombinant baculovirus infection (Lanford et al 1989). Our findings in terms of HBsAg synthesis were comparable to those reported for Lepidoptera cells using the baculovirus expression system (Kang et al 1987;Lanford et al 1989) or mouse cells transfected using a bovine papilloma virus vector system (Hsiung et al 1984). Our approach allowed us to obtain HBsAg expression levels comparable to those previously published (Deml et al 1999).…”
Section: Discussionsupporting
confidence: 78%
“…Lower levels of expression have been reported for vectors that do not have all of the upstream sequences of the polyhedrin promoter (Matsuura et al, 1986(Matsuura et al, , 1987. Low level expression has been observed for certain gene products irrespective of the vector used (including the HBsAg, Kang et al, 1987;see below); the reason for the lower expression is not known.…”
Section: Introductionmentioning
confidence: 94%
“…35 mm dishes), the level of HBsAg synthesis by the recombinant baculovirus HBsYK 14 (Kang et al, 1987) has been reported to be equivalent to 1.5 mg per 109 infected cells. In large culture volumes (100 to 1000 ml), expression levels of the order of 0.3 to 0-5 mg per 109 infected ceils are obtained with the same virus.…”
Section: Recombinant Baculoviruses That Express Hbcag or Hbpcag Or Hbsagmentioning
confidence: 99%
See 2 more Smart Citations